Pengaruh Pemilihan Kala Ulang Debit Banjir Rancangan Metode HSS Nakayasu Terhadap Dimensi Sand Pocket di Gunung Merapi - Imam Sudrajad; Yeri Sutopo; Agung Sutarto (Universitas Tribhuwana Tunggadewi Malang, 2020)
Design flood discharge has become an important parameter in hydraulic construction design planning. When analyzing it, return period selection is crucial because it will determine the amount of design flood discharge. The return period selection is adjusted to the characteristics of the Watershed (DAS). The Sand Pocket planning location is in Woro River, Klaten, Central Java. The unavailability of design flood discharge data at the observation site resulted in the design flood discharge analysis being carried out. This study focuses on comparing the magnitude of design flood discharges from different return periods, namely Q5th, Q10th, Q25th, Q50th, and Q100th. After the flood discharge is obtained, it is utilized to calculate the dimensions of the Sand Pocket construction. Each return period used in this study produced different dimensions of the building in several parts. This analysis shows the different dimensions of the building due to differences in flood discharge generated, namely the Main Dam and Sub Dam parts including effective height, upstream slope (m), flow height above the lighthouse, freeboard, foundation depth, and base. In the part of apron, there are differences of floor length and thickness dimension. The difference dimensions also appeared on the upstream side slope of Main Dam and Sub Dam. This return period selection determines the amount of the design flood discharge that will affect the dimensions of the Sand Pocket that will be planned.